Regimes fiscais na indústria do petróleo: a influência de características contratuais na atratividade econômica de projetos de exploração e produção - Soares, Lucas Santana Furtado (2017)
The Oil industry is known to be one of the most profitable industries in the world. A key challenge for all oil-production country is to stay attractive for business without giving up the extreme large oil rents. Designing a good fiscal system is a necessary condition in order to maintain the balance between companies and Government goals or requirements. In 2013, Brazil legislation changed in other to implement a new production share fiscal system that would coexist with the 1998 concession system. This type o change is easily seen in the regulatory framework history of other countries. There is a dedicated section with examples of regulatory mechanisms for rent capture. This work focus on the study of a country oil and gas fiscal system and its influence on the E&P project attractiveness. An engineering development model is designed for a presalt carbonate reservoir located at ultra deep waters (the type of reservoir covered by the new partition share contract). It is also discussed that the difference among all the fiscal system is, majorly, the oil property and the payment method. Apart from that, one can make the outputs of a concession system become equivalent to a production sharing system simply by changing the inputs. A cash flow curve is calculated for each engineering model for different field volumes in each type of contract. This mean that the cash flow curve is more than a simple mathematical function, its is modeled in order to reflect the operational reality of an oil field. Each cash flow, and its net present value, are linked with its fiscal system characteristics. Finally, the differences between the cash flow net present value are the base for a critical analysis about the each fiscal system. At the final section, an analysis is performed in order to compare different fiscal systems on an exploratory framework. Finally, it is discussed the exploratory risks and its influence on the attractiveness of private capital in public bids.